The burden of illness in Prader-Willi syndrome: a systematic literature review - Dairine Dempsey; Maria Hall; Ben Lanning; Ben Barron-Millar; Michael Huang; Neil Cowen; Mitch Nagao; Raj Gandhi; Anish Bhatnagar (Orphanet Journal of Rare Diseases)
Abstract Background Prader-Willi syndrome (PWS) is a rare, genetic neurobehavioral and metabolic disorder marked by hyperphagia, behavioral challenges, and significant comorbidities, requiring a multidisciplinary approach for effective management. This systematic review aimed to comprehensively evaluate the burden of disease associated with PWS, focusing on mortality, healthcare resource utilization, economic burden, and quality of life. Methods The literature search, conducted on August 13, 2024, included the MEDLINE, Embase, and Cochrane Library databases, as well as conference proceedings. Original studies published since 2014 were selected based on relevance to PWS patient burden, covering mortality, humanistic and economic impacts. Data from the selected studies were extracted, and currency conversions were standardized. Results For the topics of mortality, humanistic burden and economic burden, a total of 11 studies, 95 studies, and 33 studies were included, respectively. Individuals with PWS faced significantly reduced life expectancy compared to the general population, with leading causes of death including respiratory failure, consequences of uncontrolled hyperphagia, and cardiovascular complications. Hyperphagia contributed substantially to the disease burden, necessitating constant food security measures to prevent life-threatening complications. Primary caregivers, predominantly parents of individuals with PWS, experienced significant emotional and psychological strain. The time-intensive responsibilities of implementing food security measures heavily impacted their daily lives, social and family dynamics, as well as their financial health. Quality of life for patients was less frequently reported but markedly impaired, driven by physical health challenges, behavioral issues, and social isolation. Wider family dynamics were also often impacted, with siblings reporting increased psychosocial stress and feelings of neglect. The direct costs of managing PWS, including frequent hospitalizations and specialized care, were consistently reported to exceed those of matched controls without PWS, highlighting the substantial economic burden associated with the condition. Conclusion This systematic literature review highlights the profound burden of PWS on patients, caregivers, payers of care, and healthcare systems. Complications of PWS reduce life expectancy, impair quality of life, and impose considerable financial strain. The findings underscore an urgent need for comprehensive support and innovative treatments that address the complex manifestations and consequences of PWS, particularly hyperphagia, to improve outcomes for patients and their families.